A comparison between 24‐hour decays and Butler–Volmer Corrosion Rates. Issue 9 (10th April 2019) - Atkins, Chris; Merola, Rudi; Lambert, Paul
Abstract: Twenty‐four‐hr decays are commonly used to assess the performance of cathodic protection on reinforced concrete. This approach has been empirically demonstrated by the performance of systems in the field. More recently an approach has been used to extrapolate corrosion rates from the decays and applied current density. This paper compares the two approaches using laboratory data and field data from a large number of cathodically protected structures to assess the natural variability in potentials and corrosion rates. Abstract : Twenty‐four‐hr decays are commonly used to assess the performance of cathodic protection on reinforced concrete. This approach has been empirically demonstrated by the performance of systems in the field. More recently an approach has been used to extrapolate corrosion rates from the decays and applied current density. This paper compares the two approaches using laboratory data and field data.